2008
DOI: 10.1038/embor.2008.21
|View full text |Cite
|
Sign up to set email alerts
|

The RhoA‐associated protein Citron‐N controls dendritic spine maintenance by interacting with spine‐associated Golgi compartments

Abstract: Dendritic spines are highly dynamic protuberances that are thought to be crucial for learning and memory. Although it is well known that actin filaments and membrane dynamics regulate spine plasticity, how these two events are linked locally is less clear. Here, we provide evidence that Citron-N (CIT-N), a binding partner of the small GTPase RhoA, is associated with the actin filaments and Golgi compartments of dendritic spines. We also show that CIT-N is required for recruiting F-actin and Golgi membranes at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 12 publications
3
17
0
Order By: Relevance
“…Moreover, phosphodiesterase 4D (PDE4D) a major regulator of cAMP levels, which is decreased in Disc1 mutant mice (Kvajo et al, 2011), is also associated with the Golgi apparatus (Verde et al, 2001), raising the possibility that Disc1 may be part of macromolecular complexes regulating cAMP in this cellular compartment. Importantly, the Golgi apparatus and post-Golgi trafficking have critical roles in dendrite and axonal growth, and spine morphogenesis (Horton et al, 2005; Rosso et al, 2004; Camera et al, 2008). Thus, Disc1-mediated impairments in aspects of Golgi-related metabolism may adversely affect dendritic growth.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, phosphodiesterase 4D (PDE4D) a major regulator of cAMP levels, which is decreased in Disc1 mutant mice (Kvajo et al, 2011), is also associated with the Golgi apparatus (Verde et al, 2001), raising the possibility that Disc1 may be part of macromolecular complexes regulating cAMP in this cellular compartment. Importantly, the Golgi apparatus and post-Golgi trafficking have critical roles in dendrite and axonal growth, and spine morphogenesis (Horton et al, 2005; Rosso et al, 2004; Camera et al, 2008). Thus, Disc1-mediated impairments in aspects of Golgi-related metabolism may adversely affect dendritic growth.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we used a pSuper-based shRNA vector, which has been previously described, together with the appropriate control (Camera et al , 2008). HeLa cells plated on six-well plate were transfected using 1 μg of the required plasmid DNA and 3 μl Trans- IT-LT1 transfection reagent (Mirus Bio, Madison, WI), or 6.25 μl of the required siRNA (20 μM) and 2.5 μl Lipofectamine 2000 (Invitrogen, Carlsbad, CA), according to the manufacturers’ instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we have shown that the increased expression and activation of rhoA by obscurin's rhoGEF domain increases ROCK1 expression and decreases CRIK expression. ROCK1 activity in striated muscle is associated with hypertrophy and myoblast fusion (Maekawa et al, 1999;Liu et al, 2003;Nishiyama et al, 2004;Castellani et al, 2006;Peters and Michel, 2007), whereas CRIK activity is associated with cytokinesis and Golgi organization (Camera et al, 2003(Camera et al, , 2008Shandala et al, 2004;Berto et al, 2007). RhoA signaling through ROCK1 is a well-characterized pathway that is up-regulated in cardiac hypertrophy, and is responsible for many of the associated morphological changes (Molkentin and Dorn, 2001;Ahuja et al, 2007;Peters and Michel, 2007).…”
Section: Downstream Signalingmentioning
confidence: 99%